The interplay between memory and value-based risky choice - Simonsen, Nick (2023)
Most of the decisions we make in our everyday lives are based on our past experiences with similar situations. This ranges from trivial decisions, such as deciding which snack to buy while grocery shopping, to more complex decisions, like how to best invest your money or where to go on holiday. In this thesis, I present findings from a series of empirical studies examining how people integrate information into memory and utilize it in subsequent choices. Specifically, the experimental studies presented in this thesis examined how people encode and treat task-relevant and task-irrelevant information, allocate attention to available choice options, and assess the temporal dynamics of risky choice. Across all experimental studies, I also examine how formation integration changes with learning. Together, the work presented in this thesis provides theoretical advances to our understanding of how memory and decision-making interact and shape each other.